Simulasi Pengaruh Jumlah dan Sudut Sudu Terhadap Efisiensi dan Daya Turbin Air Aksial - Fattah, Hamidah Nurrul; Finahari, Nurida; Ismail, Nova Risdiyanto (Widyagama University of Malang, 2024)
The amount of electrical energy needed each year is increasing, while the source of electrical energy is decreasing each year. So that alternative resources are needed, namely renewable energy, to help meet the current need for electrical energy. One of the renewable energies that is currently widely used is the water turbine. In this study, the air turbine will be studied with the aim of determining the efficiency and power of the turbine with variations in the number of blades (10, 14 and 18), variations in the blade angle of 10⁰, 15⁰, 20⁰, 25⁰, 30⁰, 35⁰, 40⁰, 45⁰, and using various types of axial turbines. The study produced the highest efficiency value of 99.94% in the Francis type turbine with 10 blades and an angle of 20⁰. And the highest power value of 63.77 Watts is found in the Kaplan turbine with 18 blades and an angle of 10⁰.